Impact of Covid-19 on Mental Health : A Review - Rajesh Kumar Gupta; Preety Gupta; Shivani Gupta; Sumit Garg (Journal of Orofacial Research, 2021)
Tongue dysfunction in form of altered tongue rest posture and tongue tip protrusion during swallowing, go along with anterior open bite malocclusion in the majority of cases. Once the etiology of the open bite has been identified and ascribed to an abnormal posture of the tongue, orthodontists should classify tongue posture through an analysis of the morphological features of the malocclusion. The vertical orientation of the tongue at any given posture deserves equal consideration to that of its forward-thrusting potential. In cases with low tongue rest posture, only blocking mechanisms such as cribs may not solely be effective as upward elevation of the tongue is also needed to achieve normal rest posture. Contrarily, tongue stimulator appliances namely bluegrass appliances and tongue practice beads as well as my-functional therapy require a great deal of patient engagements to become clinically effective in modifying tongue behavior. We endeavor to find the therapeutic potential of a hybrid approach; that combines forward tongue restriction and vertical elevation via a composite habit breaking appliance (CHBA), in patients having low forward resting posture of the tongue. A case report has been presented to exemplify the idea.